Constitutional protection of the rights of stateless children to education in Iraqi legislation )A comparative study) - Kamel Khaled Fahd - Hind Ali Muhammad ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Protecting the rights of stateless children is one of the priorities of the international community, as children are the basic building block in building in society's structure.The beginning of their lives is characterized by weakness, frailty, and the inability to prevent the dangers facing them at a stage that is one of the most dangerous stages which has a direct impact on forming their personality in the future, and one of the effects of this is their inability to meet their necessary needs that secure them ways to continue life and keep up with it by self-reliance. Therefore, the problem of stateless children obtaining their rights is an urgent necessity that must be protected by the legislator and society to ensure one of their rights, which is the right of education. In his research, the researcher relied on the method of comparative analysis and concluded with a set of Findings and proposals.